New Concepts on Reversibility and Targeting of Liver Fibrosis; A Review Article - Hedyeh Ebrahimi; Mohammadreza Naderian; Amir Ali Sohrabpour (Middle East Journal of Digestive Diseases, 2018)
Currently, liver fibrosis and its complications are regarded as critical health problems. With the studies showing the reversible nature of liver fibrogenesis, scientists have focused on understanding the underlying mechanism of this condition in order to develop new therapeutic strategies. Although hepatic stellate cells are known as the primary cells responsible for liver fibrogenesis, studies have shown contributing roles for other cells, pathways, and molecules in the development of fibrosis depending on the etiology of liver fibrosis. Hence, interventions could be directed in the proper way for each type of liver diseases to better address this complication. There are two main approaches in clinical reversion of liver fibrosis; eliminating the underlying insult and targeting the fibrosis process, which have variable clinical importance in the treatment of this disease. In this review, we present recent concepts in molecular pathways of liver fibrosis reversibility and their clinical implications.